Aggression : clinical features and treatment across the diagnostic spectrum - Coccaro, Emil F.; McCloskey, Michael S. (American Psychiatric Association Publishing, 2019)
Based on the latest research, Aggression: Clinical Features and Treatment Across the Diagnostic Spectrum is designed to aid mental health practitioners in identifying and treating aggression in diverse patient presentations.